Pertanggungjawaban Hukum Penyedia Jasa Platform Digital terhadap Pelanggaran Kekayaan Intelektual - Ida Bagus Nyoman Adhi Wiguna (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
This research discusses Tokopedia's legal responsibility for each consumer if there is a mismatch between goods in online buying and selling. Even though regulations have been formed regarding the technical implementation of electronic commerce, in fact these regulations still have weaknesses in terms of legal protection because parties in electronic transactions, both sellers and buyers, are often disadvantaged by parties who violate agreements and dispute resolution provided through digital platforms is considered still detrimental to one party. The development of digital platforms has opened the door to economic and creative activities. However, this success also carries the risk of intellectual property infringement. This research will explain the background, provide the legal context, and detail the urgency of this research in the legal context in Indonesia.This research uses empirical research methods, and the approach used is a statutory approach (law) Case approach (Case) which is carried out at the level of horizontal synchronization, which measures the extent of a governing law and case.